Superstition and Women: Patriarchal Trap on Women Empowerment in Ling Shuhua’s “Mid-Autumn Eve” Title - Ajeng, Galuh Dwi; Istiara, Febriyantina; Windriani, Dian; Zulianti, Hajjah (Universitas Pamulang, 2025)
The aim of this research is to analyze about superstition as one of the characteristics of Chinese literature and how superstition is part of patriarchal agenda in oppressing women depicted in Ling Shuhua’s “Mid-Autumn Eve” translated by Marie Chan. Superstition is often manifested in Asian literature because it is part of Asian culture. By analyzing Ling Shuhua’s “The Mid-autumn Eve”, the research finds out that modern Chinese society still believes in the superstition, such as “harmony duck” that symbolizing the prosperity and eternal love; for instance, how the couple who eat the “harmony duck” in the Mid-autumn festival will live together forever. Therefore, T’ai-t’ai forces her husband to eat the duck because she is afraid that his failure in eating the duck will be an ill omen for their marriage. Through feminist perspective, superstition can lead women to fall into the trap of patriarchy. By believing in superstition, women are associated with ignorance, stupidity, and weak that needs to be excluded in men’s matter, such as decision making. In the case of Cheng-jen for instance, by letting T’ai-t’ai, her wife, takes a decision that is based on superstition, Cheng-jen faces big regret in his life; he cannot be together with his foster sister before she dies